To be or not to be a campaigning organisation: the case of the NGO ActionAid. Issue 5 (4th July 2022) - Cascant-Sempere, Mª Josep
ABSTRACT: Can a service-delivery-born development NGO become a campaigning organisation? The short answer is "yes, but". In the past decade, ActionAid made bold steps, such as shifting its global strategy towards campaigning, developing an international network of campaigners, and using non-campaign functions such as programmes and fundraising to mobilise unusual activists. However, these happened in a context of charity sector restrictions and an organigram still heavily based on programmes. This study talks to the debates about the political relevance of development NGOs, suggesting that politicisation processes often happen through "tense opportunities" where hybrid apolitical and political dimensions coexist.